Հունա-հռոմեական հատուկ անունները Մխիթարյանների հայերեն թարգմանություններում և դրանց տառադարձման նոր սկզբունքները - Թոփչյան, Արամ (Մատենադարան)
Homer’s Iliad was translated into Grabar twice, by Eghia T‘omachean (Venice, 1843) and Arsen Bagratuni (Venice, 1964). Both translators in general strove to render the Greek names correctly, Bagratuni, more successfully. There are some differences in their transliterations (e.g. Bagratuni transliterated λ by լ, while T‘omachean by ղ) and in the rendering of the Greek endings. Or the name of Achilles is transliterated in different ways, in conformity with the Greek form Ἀχιλλεύς and the Latin form Achilles, and of Ajax, in conformity with the Greek form Αἴας and the Latin Ajax. In some cases the meter forced them to omit the Greek endings. Some names, following the tradition of old translators are replaced by their Armenian equivalents, e.g. Zeus became Aramazd, Cronus – Zruan, and Aphrodite – Astghik. “Илиада” Гомера дважды переводилась на грабар, Егия Томачяном (Венеция, 1843) и Арсеном Багратуни (Венеция, 1964). Оба переводчика в целом стремились к точной передаче греческих имен, Багратуни – в большей степени. Есть некоторые различия в транслитерации (например, λ – լ у Багратуни и ղ у Томачяна) и в передаче окончаний. Или по-разному переданы имена Ахилла (по греческой форме Ἀχιλλεύς и латинской Achilles) и Аякса (по греческой форме Αἴας и латинской Ajax). Иногда стихотворный размер заставлял опускать окончания. Некоторые имена, следуя традиции древних переводчиков, заменены на армянские эквиваленты: Зевс на Арамазда, Крон на Зрвана, Афродита на Астгик.
Keywords: Պատմաբանասիրություն